British Traveler and Writer John Buchan Telfer about Imereti - Nikoleishvili, Otar (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
Among the 19th-century foreign sources that provide insights into the history, culture, and traditions of Imereti, mention must be made of the book „The Crimea and Transcaucasia; being the narrative of a journey in the Kouban, in Gouria, Georgia, Armenia, Ossety, Imeritia, Swannety, and Mingrelia, and in the Tauric range“, published in London in 1876 in two volumes. This work was authored by John Buchan Telfer, a captain in the United Kingdom fleet, a member of the Society of Antiquaries of London, and a traveler and writer. It is noteworthy that during the 1870s, Telfer spent three years in the Russian Empire and made two journeys to the Crimea and the Caucasus. While Telfer did not visit many cities and regions of Georgia during his travels to the country, I will focus here only on the section of his book that pertains to Imereti. The value of the information provided by Telfer lies in its diversity and in the firsthand impressions he gathered. Despite certain inaccuracies in Telfer’s work, „The Crimea and Transcaucasia“ must be regarded as a multifaceted and significant foreign source for studying the history of Imereti and Georgia as a whole.